Contemporary Art Biennials: Prospects and Problems : Array - Genç, Eda Aylin; Genç, Ruhet (Journal of Danubian Studies and Research, 2021)
The number of contemporary art biennials worldwide - recurring, independent, large-scale and high-budget international exhibitions - have surged since the early 1990s rendering these events key places in production, legitimization and consumption of works created by artists from all over the world. In addition, mediating between culture and changing social and political issues is included in the discourse of art biennials. Globalization has both increased the engagement of non-Western peripheries in the culture industry and homogenized the artwork presented in the art biennials. This article proposes an analysis of biennials through a review of existing literature in the context of contemporary art biennials. Legitimization and promotion of artworks through marketing and branding strategies are presented along with the cultural dominance prevailing in these periodic events.